Seismic Performance Evaluation of Village Buildings in Wenzhou - Yang, Ke Jia; Li, Wei; Yin, Jian Wei (Applied Mechanics and Materials, 2012)
Earthquakes cause severe damage to structures and economic losses recently, based on which investigations are carried out on village buildings in Wenzou. Investigation results show that cavity wall structures are the most widely used by village buildings. So a typical cavity wall structure is selected for analyses in this paper. The typical structure is simulated using Sap2000. The structure was analyzed with and without structural columns and ring beams. Analyses results show that the prototype structure is inadequate to resist earthquake load. Structural columns and ring beams can enhance its seismic performance and provide it adequate seismic performance. So it is necessary to enhance village structures with structural measures.